Pharmacodynamics of TRPV1 Agonists in a Bioassay Using Human PC-3 Cells - Daniel Alvarez-Berdugo; Marcel Jiménez; Pere Clavé; Laia Rofes (The Scientific World Journal)
Purpose. TRPV1 is a multimodal channel mainly expressed in sensory neurons. We aimed to explore the pharmacodynamics of the TRPV1 agonists, capsaicin, natural capsaicinoids, and piperine in an in vitro bioassay using human PC-3 cells and to examine desensitization and the effect of the specific antagonist SB366791. Methods. PC-3 cells expressing TRPV1 were incubated with Fluo-4. Fluorescence emission changes following exposition to agonists with and without preincubation with antagonists were assessed and referred to maximal fluorescence following the addition of ionomycin. Concentration-response curves were fitted to the Hill equation. Results. Capsaicin and piperine had similar pharmacodynamics (Emax 204.8 ± 184.3% piperine versus 176.6 ± 35.83% capsaicin, P=0.8814, Hill coefficient 0.70 ± 0.50 piperine versus 1.59 ± 0.86 capsaicin, P=0.3752). In contrast, capsaicinoids had lower Emax (40.99 ± 6.14% capsaicinoids versus 176.6 ± 35.83% capsaicin, P<0.001). All the TRPV1 agonists showed significant desensitization after the second exposition and their effects were strongly inhibited by SB366791. Conclusion. TRPV1 receptor is successfully stimulated by capsaicin, piperine, and natural capsaicinoids. These agonists present desensitization and their effect is significantly reduced by a TRPV1-specific antagonist. In addition, PC-3 cell bioassays proved useful in the study of TRPV1 pharmacodynamics.